Electronic Word-of-Mouth, Destination Image, and Tourist Visit Intention: A Study of Lemukutan Island, Indonesia - Vanesa Claudia Vina; I Made Darsana; Gusti Praminatih (Journal of Social Work and Science Education, 2026)
This study investigates the effects of electronic word of mouth (e-WOM) and destination image on tourists’ visit intention toward Lemukutan Island, West Kalimantan, an emerging marine tourism destination with limited digital promotional exposure. A quantitative research design was employed using a structured questionnaire administered to 100 respondents selected through accidental sampling between September 2025 and March 2026. The collected data were analyzed using multiple linear regression after passing validity, reliability, and classical assumption tests. The findings reveal that e-WOM and destination image simultaneously have a positive and significant effect on tourists’ visit intention (F = 48.059, p < 0.001), explaining 48.7% of the variance in visit intention (Adjusted R² = 0.487). Partially, e-WOM exerts the strongest influence (β = 0.552; t = 7.647; p < 0.001), followed by destination image (β = 0.402; t = 5.579; p < 0.001). Unlike previous studies that typically examined these variables independently or in well-established destinations, this study demonstrates their integrated effects within the context of an emerging island tourism destination characterized by limited market exposure and promotional constraints. The findings highlight the strategic importance of strengthening positive online reviews and enhancing destination image to stimulate tourists’ behavioral intentions. This study contributes to the tourism marketing literature by extending empirical evidence on tourist behavioral intention in emerging marine tourism destinations and provides practical recommendations for destination managers to optimize digital marketing strategies and destination branding.